1989
DOI: 10.1055/s-2008-1071285
|View full text |Cite
|
Sign up to set email alerts
|

The Landau-Kleffner Syndrome - Case Report and Theoretical Considerations*

Abstract: The Landau-Kleffner syndrome is an acquired condition in children consisting of aphasia and epileptic discharges in the EEG with or without clinical manifestation of epilepsy. We describe a case of a very young child whose neurologic and language development before onset of the illness was uniquely well documented. Apart from her aphasia she showed several other disturbances of higher cortical functions in the acute phase of the illness. No anatomical basis has been discovered for this disease till the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Beaumanoir (1985) states that functional disturbances in the circuit: auditory cortex, verbal integration and spoken language, could be the underlying mechanism. However, this hypothesis fails to explain the other symptoms observed in some patients (Ansink et al, 1989), thus suggesting an involvement of several parts of the brain. Nakano et al (1989), using spectral topographical mapping of the EEG, suggested that electrophysiological dysfunction of the fronto-centro-parietal areas, associated with unstable paroxysmal discharges, is the main feature of this syndrome.…”
Section: Etiologymentioning
confidence: 89%
See 1 more Smart Citation
“…Beaumanoir (1985) states that functional disturbances in the circuit: auditory cortex, verbal integration and spoken language, could be the underlying mechanism. However, this hypothesis fails to explain the other symptoms observed in some patients (Ansink et al, 1989), thus suggesting an involvement of several parts of the brain. Nakano et al (1989), using spectral topographical mapping of the EEG, suggested that electrophysiological dysfunction of the fronto-centro-parietal areas, associated with unstable paroxysmal discharges, is the main feature of this syndrome.…”
Section: Etiologymentioning
confidence: 89%
“…Different therapeutic approaches have been put forward. The seizures do not represent a major treatment problem, and no episode of status epilepticus has been observed, with the exception of the case of Ansink et al (1989). Seizures seem to subside in many patients before adulthood (Montovani & Landau, 1980).…”
Section: Treatmentmentioning
confidence: 97%
“…He remained in good condition without seizures and with a better hability to communicate. DISCUSSION LKS has been reported in association with neurocysticercosis 2 , Haemophilus influenzae type B meningitis 3 , temporal lobe tumor 4 , demyelinating lesion 5 and cerebral arteritis 6 . An autoimmune etiology has been proposed 7 , but in most cases there is no evident causal factor, as observed in the present cases.…”
Section: Casementioning
confidence: 98%
“…Some authors observe organic lesions such as mild gliosis and hippocampal sclerosis, 2 inflammation of the brain tissue, 7 ' 2 or neurocysticercosis; 24 in any case, a subjacent pathology is the origin not only of the aphasia but also of the abnormal activity of the EEG.' 7 Others, by contrast, consider a functional disorder of the brain more probable, such as electrical dysregulation in several parts of the cortex 12 or the result of a blockage of the normal auditory route to language learning. 7 Neuroradiological studies have rarely been mentioned.…”
Section: Pimentioning
confidence: 99%